How to Maintain a Digitally Literate Environtment: An Attempt to Support SDGs in Education Sector - Eva Nirtha; Yonarlianto Tembang; Serlina Boru Sinaga; Herrio Tekdi Nainggolan; Nilfred Patawaran (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Digitalization is an effort to save energy, funds and time as well as an effort to support the realization of the SDGs in the education sector. This research discusses approaches in maintaining a digitally literate environment as part of efforts to achieve the Sustainable Development Goals (SDGs), especially in the field of quality education. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews, participatory observations, and documentation. The data analysis technique uses Miles and Huberman data analysis. The results of the discussion show that maintaining a digitally literate environment is a strategic and essential step in supporting the achievement of the Sustainable Development Goals (SDGs) in the digitally literate environmental education sector that not only increases individual capacity, but also contributes to inclusive and innovative and environmentally friendly growth. To maintain a digitally literate environment, a number of actions are needed, including digital transformation. This study recommends concrete steps to encourage equitable and sustainable digital transformation in various sectors of life, especially in the education sector.